2010
DOI: 10.1590/s0102-09352010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deslorelin on the induction of estrus in anestrous bitches

Abstract: The efficacy of one or multiple doses of an injectable formulation of deslorelin (a GnRH agonist) was evaluated to induce estrus in anestrous bitches. Thirteen animals composed three groups: group 1 (n=5, single IM injection of 2mg deslorelin), group 2 (n=5, four IM injections of 2mg deslorelin in alternate days), and control group (n=3, four IM saline injections in alternate days). Daily clinical evaluations, sexual behavior, vaginal cytology, plasma progesterone concentration, ovaryhysterectomy and macroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…In disagreement with these results, in the present study, we observed an increase in the average rate of 15-20% of SCI accompanied by a moderate increase in serum E2 concentrations in four of the nine treated bitches during the first eight weeks after the implant placement. Similar to our findings, Lanna et al 23 reported an increase in the proportion of superficial cells, reaching a high average of 44±15% without clinical signs of estrus in adult bitches received a single intramuscular injection of 2 mg deslorelin. In our study, dogs in the control group (G3) did not show an increase in SCI or P4 and E2 concentrations which comparable to anestrus during the observation period.…”
Section: Discussionsupporting
confidence: 92%
“…In disagreement with these results, in the present study, we observed an increase in the average rate of 15-20% of SCI accompanied by a moderate increase in serum E2 concentrations in four of the nine treated bitches during the first eight weeks after the implant placement. Similar to our findings, Lanna et al 23 reported an increase in the proportion of superficial cells, reaching a high average of 44±15% without clinical signs of estrus in adult bitches received a single intramuscular injection of 2 mg deslorelin. In our study, dogs in the control group (G3) did not show an increase in SCI or P4 and E2 concentrations which comparable to anestrus during the observation period.…”
Section: Discussionsupporting
confidence: 92%
“…The progressive sP4 increment, indirectly suggests that luteinization occurs in response to LH amplitude and that frequency pulses rise. On day 10.2±2.8, all bitches reached sP4 levels of 1.5-2.5 ng/mL, in agreement with reports using others GnRH agonists or deslorelin (Concannon et al 2006, Lanna et al 2010, Fontaine et al 2011, Walter et al 2011. sP4 declined to < 1 ng/mL after artificial insemination in 100% of bitches, indicating no corpora lutea formation and ovulation failure.…”
Section: Discussionsupporting
confidence: 88%
“…It also presents the disadvantage of having to perform an incision in the skin to remove the implant. One study (Lanna et al 2010) using a slow-release injectable form of DA 2 achieved 100% of estrus induction, to 2 mg im/48 h four times, without producing unwanted side effects at the site of injection. Concannon et al (2006) have used another GnRH agonist (lutrelin) with the same power as DA, proposed a dose of 0.6 μg/k (0.2-1.2 μg/k) with an efficiency of 92% in oestrus induction and 100% pregnancy rate, suggesting that this same DA dose can be used, to obtain similar results for a oestrus induction protocol in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…На противагу цьому Arlt et al (2015) повідомляє про появу кіст після застосування імпланту Супрелорін, а Borges et al (2015) вказує про появу кіст у поодиноких сук після декількаразового застосування імпланту. Lanna et al (2010) зазначає, що при застосування деслореліну в ін'єкційній формі 3/10 сук, які отримували препарат, відчували біль і отримали легкий набряк після в/м ін'єкцій. Наші результати вказують на те, що при застосуванні імпланту Супрелорін не спостерігалось жодних місцевих ускладнень чи негативних ефектів від підшкірного застосування імплантату, не було негативних наслідків у сук у вигляді кіст яєчників чи піометри, статевий цикл проходив схоже з природною тічкою і суки почувались добре.…”
Section: обговоренняunclassified